The ageing joint-standard age- and sex-related values of bone erosions and osteophytes in the hand joints of healthy individuals. Issue 7 (July 2019) - Berlin, A.; Simon, D.; Tascilar, K.; Figueiredo, C.; Bayat, S.; Finzel, S.; Klaus, E.; Rech, J.; Hueber, A.J.; Kleyer, A.; Schett, G.
Summary: Objective: To analyze the age-related changes of the physiological hand joint architecture. Method: To address this concept, healthy individuals (each 10 women and 10 men in six different age decades spanning from 21 to 80 years) were recruited through a field campaign, investigated for the absence of rheumatic diseases and other comorbidities and received high-resolution quantitative computed tomography (HR-pQCT) examination of the hand joints. Number and extent of erosions and osteophytes were quantified across the ages and different sexes. Results: Bone erosions [median (Q1–Q3), 1 (0–2)] and osteophytes [2 (1–4)] were found in healthy women and men with no significant sex differences. Structural changes however accumulated with age: the overall incidence rate ratio (IRR) for the number of erosions and osteophytes per age were 1.04 (95% CI: erosions 1.03–1.06; osteophytes: 1.03–1.05). This means a 4% increase in the number of erosions and osteophytes per year. Using third decade as reference, healthy individuals in the age decades from 50 years had higher IRR for erosion numbers (sixth, seventh, eigth decade: 4.87 (2.20–11.75), 6.81 (3.08–16.46) and 6.92 (3.11–16.79)) compared to younger subjects (fourth, fifth decade: 1.80 (0.69–4.87), 1.53 (0.59–4.10)). The IRRs of osteophytes also indicate a gradual increase after the fifth decade, with IRRs of 2.32 (1.32–4.17), 4.17 (2.38–7.49) and 6.86 (3.97–12.20) for the sixth, seventh and eigth decades, respectively. Conclusions: Structural changes in the hand joints of healthy individuals are age dependent. While being rare under 50 years of age, erosions and osteophytes accumulate above the age of 50, suggesting that the threshold between "normal" and "pathological" is shifted with the increase of age.